ACCUMULATION D’OSMOTICUMS CHEZ LE BLE DUR (Triticum durum Desf.) SOUS STRESS HYDRIQUE - Chaib, Ghania; Benlaribi, Mostefa; Hazmoune, Tahar (European Scientific Journal, ESJ, 2015)
In this work, the contents of proline and soluble sugars are estimated under different levels of water deficit: 75%, 35%, 25% and 12,5% of fields’ capacity (FC). The study involved 10 genotypes of durum wheat (Triticum durum Desf) of different origins, local and introduced. The results show that the proline content in the leaves is low at 75% FC. The proline increases in parallel with the decrease of the water content in the medium of development, with the exception of 25% FC; however, this increase remains normal over 75% FC. Sugars evolve in the same manner as proline for 35% and 25% FC, except that for 12.5% FC, the content is the same as 75% FC. The varieties are classified into three categories: sensitive, less sensitive and tolerant to water shortage. The accumulation of osmolytes (sugars and proline) is regarded as a biochemical marker of water stress.